Training Needs Analysis using Student Feedback Survey (SFS) results: a case study at the Department of Human Sciences - Shamshi, Asmiza; Zabri, Jefri Khairil; Abdullah, Shamsuddin (Centre of Foundation Studies, IIUM, 2024)
A Training Need Analysis (TNA) is crucial in planning training programmes to make sure academic staff are well-equipped with the needed knowledge, skills and attitude to perform their tasks well. Currently, the Department of Human Sciences (DHS) plans training programmes for staff based on requests by academic staff and on a case-by-case basis. There has yet to be a TNA that is based on the Students Feedback Survey (SFS) which may also provide important perspective for the students on what academic staff needs to improve. The purpose of this paper is to conduct a TNA based on results from SFS as an evidence-based approach utilising the perspective of students. The anonymous SFS results of academic staff from the DHS were used to find out which knowledge, skills and attitudes need improvement the most using inferential statistics. The predicted results suggested that the academic staff of DHS requires more training in encouraging students to ask questions. The paper will contribute practically to the improvement of conducting TNA that considers students’ feedback. Keywords. Training needs analysis, student feedback survey, academic professional development, evidence-based management, case study.